Preparation and In Vivo Expression of CS-PEI/pCGRP Complex for Promoting Fracture Healing - Chun-Liang Li; Feng Qin; Rong-rong Li; Jia Zhuan; Hai-Yong Zhu; Yu Wang; Kai Wang (International Journal of Polymer Science)
Background/Objective. CGRP is a calcitonin gene-related peptide that is capable of promoting bone development and bone regeneration. Chitosan is a nontoxic and degradable biomaterial. However, the gene transfection efficiency of chitosan is low, whereas PEI (polyethyleneimine) has higher capability of transfection efficiency. In this paper, PEI was covalently linked to chitosan, and the rat CGRP plasmid was encapsulated in a CS-PEI complex to construct CS-PEI/pCGRP nanoparticles. The characterization and biological effects of CS-PEI/pCGRP nanoparticles were investigated in vivo. Methods. CS-PEI/pCGRP nanoparticles were prepared by a complex coacervation method. The PEI distribution degree on chitosan was measured with a dialysis method and 1H-NMR analysis. The particle size and zeta potential of CS-PEI/pCGRP nanoparticles were detected by dynamic light scattering. The binding of CS-PEI to pCGRP was detected by gel retardation assay. The transfection effect was evaluated by RT-qPCR. A rat femoral fracture model was established and treated with PBS, pCGRP, CS-PEI, and CS-PEI/pCGRP to detect the expression of CGRP and downstream genes in early healing of fractures by RT-qPCR, western blot, and immunohistochemistry (IHC). Results. The particle size and zeta potential of CS-PEI/pCGRP nanoparticles were stable when the mass ratio of CS-PEI and pCGRP was higher than 5 : 1, the ratio which could also effectively protect pCGRP from DNase I degradation. CS-PEI/pCGRP could obviously increase CGRP expression in rat bone marrow stromal cells. In vivo fracture healing experiments demonstrated that CGRP could be delivered to the body via the CS-PEI and expressed in situ after a 3-week treatment. Moreover, CS-PEI/pCGRP significantly enhanced the mRNA and protein levels of downstream RUNX2 and ALP. Conclusion. CS-PEI/pCGRP nanoparticles were an effective nonviral gene transfection system that could upregulate CGRP expression in vivo and accelerate the expression of key biomarkers for early healing of fractures.